2008
DOI: 10.1016/j.neuroimage.2008.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Increased cortico-cortical functional connectivity in early-stage Parkinson's disease: An MEG study

Abstract: We set out to determine whether changes in resting-state corticocortical functional connectivity are a feature of early-stage Parkinson's disease (PD), explore how functional coupling might evolve over the course of the disease and establish its relationship with clinical deficits.Whole-head magnetoencephalography was performed in an eyesclosed resting-state condition in 70 PD patients with varying disease duration (including 18 recently diagnosed, drug-naive patients) in an "OFF" medication state and 21 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
147
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 43 publications
15
147
1
1
Order By: Relevance
“…In very early stage, untreated, non-demented patients, we recently found increased alpha1 synchronization (Stoffers et al 2008). In moderately advanced patients, the increase in functional connectivity involved a more extended frequency range, also including the theta, alpha2 and beta bands (Stoffers et al 2008).…”
Section: Pddmentioning
confidence: 85%
See 3 more Smart Citations
“…In very early stage, untreated, non-demented patients, we recently found increased alpha1 synchronization (Stoffers et al 2008). In moderately advanced patients, the increase in functional connectivity involved a more extended frequency range, also including the theta, alpha2 and beta bands (Stoffers et al 2008).…”
Section: Pddmentioning
confidence: 85%
“…However, for the UPDRS OFF scores, there were no significant results nor even a trend towards significance for any of the SL parameters in the ANOVA with repeated-measures in both the demented and non-demented PD group. Furthermore, previous studies have shown that impaired motor function in early as well as more advanced stage, non-demented PD patients is associated with increases in synchronization (Silberstein et al 2005;Stoffers et al 2008)). Since, in the present study, we mainly report significant reductions in the demented patients, it seems highly unlikely that our results can be explained by worse motor function in our demented patients.…”
Section: Pddmentioning
confidence: 98%
See 2 more Smart Citations
“…Here the brain was described as a complex network, and graph theory was used to characterize the structure and dynamics of relevant networks. With such methods, Stoffers et al (2008) observed that the increased resting-state functional connectivity in alpha range was a feature of PD from the earliest clinical stages, and the increases in theta or beta bands appeared later in the disease; Utianski et al (2016) recently found that the network alteration and breakdown was the robust attribute of the pathophysiology of PD cortical dysfunction.…”
Section: Introductionmentioning
confidence: 99%